Risk factors for regional lymph node metastasis in rectal neuroendocrine tumors: a population-based study - Li, Ruizhen; Li, Xiaofen; Wang, Yan; Chang, Chen; Lv, Wanrui; Li, Xiaoying; Cao, Dan (Frontiers in Medicine, 2024)
The identification of risk factors for regional lymph node (r-LN) metastasis in rectal neuroendocrine tumors (R-NETs) remains challenging. Our objective was to investigate the risk factors associated with patients diagnosed with R-NETs exhibiting r-LN metastasis. Patient information was obtained from the Surveillance, Epidemiology, and End Results (SEER) database, complemented by data from the West China Hospital (WCH) databases. The construction cohort comprised patients diagnosed with R-NETs from the SEER database, while cases from the WCH database were utilized as the validation cohort. A novel nomogram was developed to predict the probability of r-LN metastasis, employing a logistic regression model. Univariate analysis identified four independent risk factors associated with poor r-LN metastasis: age (HR=1.027, P < 0.05), grade (HR=0.010, P < 0.05), T stage (HR=0.010, P < 0.05), and tumor size (HR=0.005, P < 0.05). These factors were selected as predictors for nomogram construction. The novel nomogram serves as a reliable tool for predicting the risk of r-LN metastasis, providing clinicians with valuable assistance in identifying high-risk patients and tailoring individualized treatments.